Knee joint strength ratios and effects of hip position in rugby players - Deighan, M. A.; Serpell, B. G.; Bitcon, M. J.; de Ste Croix, M. (The Journal of Strength and Conditioning Research, 2012)
Measures of knee joint function, although useful in predicting injury, can be misleading because hip position in traditional seated isokinetic tests is dissimilar to when injuries occur. This study aimed to determine the differences between seated and supine peak torques and strength ratios and examine the interaction of position with joint velocity. This was a cross-sectional, repeated measures study. Isokinetic knee extensor and flexor concentric and eccentric peak torque was measured seated and supine (10° hip flexion) at 1.04 and 3.14 rad/s in 11 Rugby players. Repeated measures analysis of variance and paired t-tests were used to analyze peak torques and strength ratios. Bonferroni post hoc, limits of agreement, and Pearson's correlation were applied. Seated peak torque was typically greater than that for supine for muscle actions and velocities. The values ranged from 109 ± 18 N/m (mean ± s) for supine hamstring concentric peak torque at 1.04 rad/s to 330 ± 71 for seated quadriceps eccentric peak torque at 1.04 rad/s. There was a significant position × muscle action interaction; eccentric peak torque was reduced more than concentric in the supine position. Knee joint strength ratios ranged from 0.47 ± 0.06 to 0.86 ± 0.23, with a significant difference in means between supine and seated positions for functional ratio at 3.14 rad/s observed; for seated it was 0.86 ± 0.23; and for supine, it was 0.68 ± 0.15 (p < 0.05). Limits of agreement for traditional and functional ratios ranged from 1.09 ×/÷ 1.37 to 1.13 ×/÷ 1.51. We conclude that hip angle affects isokinetic peak torques and knee joint strength ratios. Therefore, the hip angle should be nearer 10° when measuring knee joint function because this is more ecologically valid. Using similar protocols, sports practitioners can screen for injury and affect training to minimize injury.